Lipoprotein subfractions by nuclear magnetic resonance are associated with tumor characteristics in breast cancer. Issue 1 (December 2016) - Flote, Vidar; Vettukattil, Riyas; Bathen, Tone; Egeland, Thore; McTiernan, Anne; Frydenberg, Hanne; Husøy, Anders; Finstad, Sissi; Lømo, Jon; Garred, Øystein; Schlichting, Ellen; Wist, Erik; et al.
Abstract Background High-Density Lipoprotein (HDL)-cholesterol, has been associated with breast cancer development, but the association is under debate, and whether lipoprotein subfractions is associated with breast tumor characteristics remains unclear. Methods Among 56 women with newly diagnosed invasive breast cancer stage I/II, aged 35–75 years, pre-surgery overnight fasting serum concentrations of lipids were assessed, and body mass index (BMI) was measured. All breast tumors were immunohistochemically examined in the surgical specimen. Serum metabolomics of lipoprotein subfractions and their contents of cholesterol, free cholesterol, phospholipids, apolipoprotein-A1 and apolipoprotein-A2, were assessed using nuclear magnetic resonance. Principal component analysis, partial least square analysis, and uni- and multivariable linear regression models were used to study whether lipoprotein subfractions were associated with breast cancer tumor characteristics. Results The breast cancer patients had following means: age at diagnosis: 55.1 years; BMI: 25.1 kg/m2 ; total-Cholesterol: 5.74 mmol/L; HDL-Cholesterol: 1.78 mmol/L; Low-Density Lipoprotein (LDL)-Cholesterol: 3.45 mmol/L; triglycerides: 1.18 mmol/L. The mean tumor size was 16.4 mm, and the mean Ki67 hotspot index was 26.5 %. Most (93 %) of the patients had estrogen receptor (ER) positive tumors (≥1 % ER+), and 82 % had progesterone receptor (PgR) positive tumors (≥10 % PgR+). Several HDL subfraction contents were strongly associated with PgR expression: Apolipoprotein-A1 (β 0.46, CI 0.22–0.69, p  < 0.001), HDL cholesterol (β 0.95, CI 0.51–1.39, p  < 0.001), HDL free cholesterol (β 2.88, CI 1.28–4.48, p  = 0.001), HDL phospholipids (β 0.70, CI 0.36–1.04, p  < 0.001). Similar results were observed for the subfractions of HDL1-3. We observed inverse associations between HDL phospholipids and Ki67 (β -0.25, p  = 0.008), and in particular between HDL1's contents of cholesterol, phospholipids, apolipoprotein-A1, apolipoprotein-A2 and Ki67. No association was observed between lipoproteins and ER expression. Conclusion Our findings hypothesize associations between different lipoprotein subfractions, and PgR expression, and Ki 67 % in breast tumors. These findings may have clinical implications, but require confirmation in larger studies.